肺高血圧症を治療するための組成物および方法 (2021)
In some aspects, the invention teaches pharmaceutical compositions that include a TGF-β ligand trap, and methods of using a TGF-β ligand trap to treat, prevent, or reduce the progression rate of pulmonary hypertension (PH). The invention also provides methods of using a TGF-β ligand trap to treat, prevent, or reduce the progression rate of a variety of conditions including, but not limited to, pulmonary vascular remodeling, pulmonary fibrosis, right ventricular hypertrophy, diseases associated with excessive TGF-β signaling, diseases associated with excessive GDF15 signaling, and diseases associated with excessive PAI-1 signaling. The invention further provides methods of using a TGF-β ligand trap to reduce right ventricular systolic pressure in a subject.